Lexicons in Baris Demang Demung Dance Costumes at Banjar Tegal Village - Kd Astri Nirwitta Wijayanti; I Gede Budasi; Putu Eka Dambayana S (Universitas Pendidikan Ganesha, 2022)
Baris Demang Demung dance is a sacred dance that exists at Banjar Tegal Village, Singaraja, Bali. This study was designed in a descriptive qualitative study. The focus of this study was to find out the lexicons and the cultural meaning of costumes used by the dancers of Baris Demang Demung dance. This study applied observation and interview methods to collect the data and totally supported with the three selected informants. The obtained data were analyzed qualitatively and descriptively. The result of this study showed that t here were 27 lexicons in the dance costumes which were divided into three types namely costumes in Baris Demang Demung (8 lexicons), costumes in Prebangsa/King (14 lexicons), and costumes in Potet (10 lexicons). However, 5 of the same lexicons are found in Prebangsa/King and Potet costumes. Therefore, it can be said that there were 27 lexicons found in costumes.